Lifestyle and Medicine in the Enlightenment The Six Non-Naturals in the Long Eighteenth Century (Taylor & Francis, 2020)
lifestyle; medicine; enlightenment; eighteenth century; history
English
Keywords: History; lifestyle; medicine; enlightenment; eighteenth century; history